Analysis of the Implementation of Maryam Exercise in Prenatal Classes to Increase the Rate of Normal Deliveries at Fahri Mutiara Clinic, Asahan Regency, in 2025 - FAHRI YANTI; Karnirius Harefa; Raisha Octavariny (JURNAL KESMAS DAN GIZI (JKG), 2026)
Background: The childbirth process is an emotional experience that involves both physical and psychological mechanisms in mothers giving birth. Normal delivery is often a tense event for most women. A mother, especially one experiencing her first pregnancy (primigravida), tends to feel fear when facing childbirth because it is her first experience. When this fear arises, the brain automatically triggers the body to anticipate pain, making the pain during labor feel more intense. Each individual’s anxiety reaction varies depending on personality, emotional condition, level of understanding, cultural background, family support, education, and prior experiences. Objective: This study aims to describe and analyze the implementation of the Maryam exercise in prenatal classes to increase the rate of normal deliveries at the Fahri Mutiara Clinic, Asahan Regency, in 2025. Methods: qualitative with a case study approach, focusing on gathering detailed information. Result: Based on interviews with informants (IF1–IF7), pregnant women’s perceptions of the benefits of the Maryam exercise at Fahri Mutiara Clinic were very positive. This exercise was considered helpful in preparing both physically and mentally for childbirth. The motivation of pregnant women to participate was driven by the desire to give birth normally, reduce anxiety, and maintain the health of both mother and baby, supported by their husbands, healthcare workers, and the surrounding environment. Conclusion: The role of the midwife instructor was highly significant as a guide, motivator, and educator throughout the sessions. Mothers who regularly participated in the exercise reported calmer childbirth experiences, better breath control, and smoother labor without complications, along with increased inner peace and self-confidence.